Energetic degeneracy and electronic structures of germanium trimers doped with titanium - Phạm, Lê Nhân (AIP Publishing, 2021)
Geometries and electronic structures of germanium trimer clusters doped with titanium TiGe3−/0 were studied making use of the complete active space self-consistent field followed by second-order perturbation theory, explicitly correlated coupled cluster singles and doubles method with perturbative triples corrections CCSD(T)-F12, and Tao-Perdew-Staroverov-Scuseria methods. Two electronic states (2A′ and 2A″) of the anion (pyramid shape) were determined to be nearly degenerate and energetically competing for the anionic ground state of TiGe3−. These two anionic states are believed to be concurrently populated in the experiment and induce six observed anion photoelectron bands. Total 14 electronic transitions starting from the 2A′ and 2A″ states were assigned to five out of six visible bands in the experimental anion photoelectron spectrum of TiGe3−. Each band was proven to be caused by multiple one-electron detachments from two populated anionic states. The last experimental band with the highest detachment energy is believed to be the result of various inner one-electron removals.